2022
DOI: 10.3991/ijet.v17i08.29811
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Students' Learning Patterns in Online Learning Environments: A Literature Review

Abstract: Digital learning environments have offered new opportunities to stream educational materials such as courses, educational videos, forums and provide outcomes of the students, grades, engagement details, and learning patterns. These valuable educational data has emerged with the latest technologies and software tools to provide researchers and decision-makers with a better understanding of students' behaviours. These virtual learning environments can professionally aid struggling students by observing, learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Ong et al (2021) concluded that learners who interact during class discussions with their teacher and peers complete and pass the subject successfully. Therefore, it is imperative to consider the logistical requirements of particular online instructional designs, such as the compatibility of the device, bandwidth for accessing the learning management system, participating in synchronous sessions, accessing learning materials, and using specific content formats like videos (Ali et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al (2021) concluded that learners who interact during class discussions with their teacher and peers complete and pass the subject successfully. Therefore, it is imperative to consider the logistical requirements of particular online instructional designs, such as the compatibility of the device, bandwidth for accessing the learning management system, participating in synchronous sessions, accessing learning materials, and using specific content formats like videos (Ali et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…VR technology immerses the user in an experience rather than merely observing a screen in front of them. Users can interact with a 3-dimensional world using multiple senses, including sight and even touch, facilitated by wearing VR glasses [2]. By utilizing VR technology in science education, students can explore various scientific topics in a fun and interactive manner, including space, the solar system, human anatomy, and other scientific fields [3].…”
Section: Virtual Realitymentioning
confidence: 99%
“…Student dropouts can occur due to various factors, including family background, inadequate social connections, employment, poor relationships, lack of motivation, insufficient persistence or skills, previous academic struggles, stress, disengagement, self-evaluation issues, poor academic performance, financial hardships, unexpected external problems, classroom environment, teacher engagement, and course material, among other factors [1] [6] [7] [11] [18]. While these factors may indicate a student's risk of dropping out, gathering data, particularly sensitive data such as parental educational background and financial status, can be problematic.…”
Section: Design Of a Machine Learning Model To Predict Student Attritionmentioning
confidence: 99%